The association of vitamin e supplementation and mortality – finally consistent results of statistical analysis. Re: the questionable association of vitamin e supplementation and mortality – inconsistent results of different meta-analytic approaches - GeríŸ, J. (Cellular and Molecular Biology, 2010)
Abstract